Perfectionism And Overexcitability: Uniqueness Or Lack Of Socioemotional Development Of Gifted And Talented Students? - Amnah Zanariah Binti Abd Razak; Bakar. A. Y. A.; Surat, S.; Majid R. A. (Allied Business Academies, 2024)
Indexed by Scopus